Pathophysiological, immunological, and inflammatory features of long COVID - Bohmwald, Karen; Diethelm-Varela, Benjamín; Rodríguez-Guilarte, Linmar; Rivera, Thomas; Riedel, Claudia A.; González, Pablo A.; Kalergis, Alexis M. (Frontiers in Immunology, 2024)
The COVID-19 pandemic continues to cause severe global disruption, resulting in significant excess mortality, overwhelming healthcare systems, and imposing substantial social and economic burdens on nations. While most of the attention and therapeutic efforts have concentrated on the acute phase of the disease, a notable proportion of survivors experience persistent symptoms post-infection clearance. This diverse set of symptoms, loosely categorized as long COVID, presents a potential additional public health crisis. It is estimated that 1 in 5 COVID-19 survivors exhibit clinical manifestations consistent with long COVID. Despite this prevalence, the mechanisms and pathophysiology of long COVID remain poorly understood. Alarmingly, evidence suggests that a significant proportion of cases within this clinical condition develop debilitating or disabling symptoms. Hence, urgent priority should be given to further studies on this condition to equip global public health systems for its management. This review provides an overview of available information on this emerging clinical condition, focusing on the affected individuals’ epidemiology, pathophysiological mechanisms, and immunological and inflammatory profiles.